Prosthetic Joint Infection Due to Histoplasma capsulatum Complicating a Total Knee Arthroplasty. (3rd August 2017) - Nowbakht, Cima; Garrity, Katherine; Webber, Nicholas; Eraso, Jairo; Ostrosky-Zeichner, Luis
Abstract: Histoplasmosis is a common pathogen but rarely reported in prosthetic joint infections. We present a case of Histoplasmosis capsulatum prosthetic joint infection along with a literature review revealing no guidelines or consensus on surgical and antifungal management. We chose the 2-stage management with an antifungal spacer and systemic oral itraconazole.